Biochemical changes in wheat induced by Chaetomium globosum against spot blotch pathogen - and D.V. SINGH, S.K. BISWAS*, K.D. SRIVASTAVA, RASHMI AGGARWAL, SHELLY PRAVEEN (Indian Phytopathology, 2003)
Application of crude extract of Chaetomium globosum hampered infection of Bipolaris sorokiniana, showing reduction in leaf blotching in wheat from 41.5 to 2.1%. Pre-inoculation sprays of the extract sensitized seedlings to produce elevated levels of total protein, soluble protein and phenol contents. New proteins of 110-kDa, 105-kDa, 38-kDa, 35-kDa and 32-kDa resolved by SDS-PAGE analysis, indicated the possibility of involvement of these proteins in the induction of host resistance in wheat.